Novel Routes for Improving Biocontrol Activity of Bacillus Based Bioinoculants - Wu, Liming; Wu, Hui-Jun; Qiao, Junqing; Gao, Xuewen; Borriss, Rainer (Frontiers in Microbiology, 2015)
Biocontrol formulations prepared from plant-growth-promoting bacteria are increasingly applied in sustainable agriculture. Especially inoculants prepared from endospore-forming Bacillus strains have been proven as efficient and environmental-friendly alternative to chemical pesticides due to their long shelf life, which is comparable with that of agrochemicals. However, these formulations of the first generation are sometimes hampered in their action and do not fulfill in each case the expectations of the appliers. In this review we use the well-known plant-associated Bacillus amyloliquefaciens type strain FZB42 as example for the successful application of different techniques offered today by comparative, evolutionary and functional genomics, site-directed mutagenesis and strain construction including marker removal, for paving the way for preparing a novel generation of biocontrol agents.